GCT-08. PROTON BEAM RADIOTHERAPY FOR PEDIATRIC AND YOUNG-ADULT PATIENTS WITH INTRACRANIAL GERM CELL TUMOR. (4th December 2020) - Sugiyama, Minako; Hashimoto, Takayuki; Mori, Takashi; Hara, Kazuya; Terashita, Yukayo; Hirabayashi, Shinsuke; Cho, Yuko; Iguchi, Akihiro; Okamoto, Michinari; Ishi, Yukitomo; Motegi, Hiroaki; Yamaguchi, Shigeru; et al.
Abstract: BACKGROUND: To reduce treatment-related adverse events in pediatric and young-adult patients with brain tumors, proton beam radiotherapy (PBT) has recently been performed instead of conventional X-ray radiotherapy. However, whether PBT is as effective as X-ray radiotherapy has not been sufficiently investigated, especially in patients receiving whole-ventricular irradiation. METHODS: We report a retrospective observation of 15 patients with intracranial germ cell tumors (GCT), who received PBT at our institution from April 2014 to September 2019. We evaluated their clinical course, short-term adverse events, and prognosis. RESULTS/ CONCLUSION: Fifteen patients (9 males and 6 females; median age 13 years) who received PBT following induction chemotherapy were analyzed. Nine patients received 23.4–27.0 GyE of whole-ventricular irradiation due to GCT in the pituitary gland, pineal body, or hypothalamic area. Three patients received 23.4 GyE of whole-brain irradiation: one of them had boost irradiation for basal ganglia. Three patients received 30.6 GyE of craniospinal irradiation (CSI). Six of the 15 patients experienced nausea (grade 2, according to the CTCAE version 4.0). Four patients, including two who received CSI, showed myelosuppression: decrease in white blood cell count, lymphocyte cell count, and neutrophil count (grade 3). No other severe short-term adverse events of >grade 2 was observed in any of the patients. At a median follow-up of 21 months (2‐62 months) after irradiation. all patients are alive without recurrence. Our results may be encouraging and further investigations with a larger scale is warranted.